The Empire Look: the installation of the British Art Exhibit at the New Zealand International Exhibition 1906-07 at Christchurch - Adams, Victoria; Tyler, Linda (Architectural History Aotearoa, 2025)
Organised under the aegis of New Zealand Premier Richard Seddon (1845-1906), the 1906-1907 New Zealand International Exhibition was designed to show the colony’s progress to the world and frame Aotearoa as a Better Britain. The British Art Section comprising 2,000 works was organised by the British government but paid for by the New Zealand government. It was housed in its own bespoke gallery in Hagley Park designed by a local architect. This installation remains the largest exhibition of British art in Aotearoa’s history, and purchases made by local government authorities formed the basis of metropolitan public art collections throughout Australasia. A principal motivation of the exhibit was to inculcate what was then considered good taste in colonial viewers, as well as to provide a version of the Royal Academy product to sell to middle-class art buyers nostalgic for reminders of Home. The British Government Representative for Fine and Applied Art, Alfred Longden (1875-1954), stated shortly after his arrival in Christchurch that the artworks were selected "with the idea of having [them] represented in the homes of the people there [New Zealand]. That is the motive that has actuated the artists. They have sent work which they feel would be suitable and acceptable for your houses and museums." Longden was also responsible for decorating the Art Gallery, fitting out the interior in an Arts and Crafts aesthetic style which was well-received by exhibition visitors. Sir Isidore Spielmann (1854-1925) who chose the works for exhibition but remained in Britain, noted in his 1907 report that "the general opinion was expressed that the rooms of the British Section were excellent in taste." The decorative scheme was also adopted for the rooms containing the Colonial Art Section, and this paper will address the ways in which the interior design framed the whole enterprise in terms of Empire.